Havana split - Bevin, Teresa (Arte Público Press, 2017)
A return to her homeland transforms the daughter of Cuban refugees who fled in the 1960s. Lara Canedo is freed from the bitterness and nostalgia of her parents, stops seeing herself as a victim and becomes one with the people.